Surveillance of Aflatoxin M1 in milk from Navsari, Gujarat area - Vyas, Trupti (Indian Journal of Dairy Science, 2021)
Aflatoxin M1 (AFM1) is produced during metabolism of Aflatoxin B1 by animal. Aflatoxin is a mutagen and carcinogen and hence possess severe health hazard problem. AFM1 can pass from animal to human via milk. Thus, AFM1 contaminated milk pose a serious threat to public health. Hence, present study deals with detection of AFM1 from cow and buffalo milk. 36 raw samples of cow and buffalo and 9 pasteurized milk samples were collected in each three season i.e., winter, summer and monsoon. Samples were extracted for AFM1 from milk. Dried samples were analyzed for AFM1 using strip ELISA test. Total of 23.81 % and 41.67 % samples from cow and buffalo respectively showed positive for AFM1. Higher numbers of samples were positive in winter followed by monsoon. None of the sample was positive for AFM1 in summer. Thus, present study revealed that there is seasonal effect on presence of AFM1 in milk sample.